PENGARUH LOAN AT RISK DAN NON-PERFORMING LOAN TERHADAP LABA USAHA MELALUI CADANGAN KERUGIAN PENURUNAN NILAI PADA PT. PEGADAIAN DI WILAYAH AREA SURABAYA 1 - Mustofa, Mustofa (Prodi Magister Manajemen Universitas Wijaya Putra, 2025)
This study aims to analyze the effect of Loan At Risk (LAR), Non-Performing Loan (NPL), and Allowance for Impairment Losses (CKPN) on operating profit performance, measured by Return on Assets (ROA). This study aims to analyze the effect of LAR, NPL, and CKPN on ROA of PT Pegadaian, and test whether CKPN is able to moderate the relationship between LAR, NPL, and ROA. This study uses secondary data from the financial statements of PT Pegadaian for the period 2019-2023 at 12 Pegadaian branch offices in Surabaya I Area. The data was analyzed using descriptive statistical analysis and multiple linear regression. The results showed that Loan At Risk (LaR) did not have a significant effect on either Operating Profit or CKPN, NPL did not have a significant effect on Operating Profit or CKPN, CKPN did not have a significant effect on Operating Profit, Loan At Risk (LaR) did not have a significant effect on Operating Profit through CKPN, and Non-Performing Loan (NPL) did not have a significant effect on Operating Profit through CKPN. The results of this study are expected to provide relevant information, especially regarding credit risk management strategies for PT Pegadaian.